2005
DOI: 10.1007/s00425-005-1488-6
|View full text |Cite
|
Sign up to set email alerts
|

Induction of some defense-related genes and oxidative burst is required for the establishment of systemic acquired resistance in Capsicum annuum

Abstract: The inoculation of primary pepper leaves with an avirulent strain of Xanthomonas campestris pv. vesicatoria induced systemic acquired resistance (SAR) in the non-inoculated, secondary leaves. This SAR response was accompanied by the systemic expression of the defense-related genes, a systemic microoxidative burst generating H2O2, and the systemic induction of both ion-leakage and callose deposition in the non-inoculated, secondary leaves. Some defense-related genes including those encoding PR-1, chitinase, osm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
67
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

6
3

Authors

Journals

citations
Cited by 84 publications
(69 citation statements)
references
References 43 publications
(47 reference statements)
1
67
0
1
Order By: Relevance
“…The induced resistance response of plants to diseases correlates intimately with the accumulation of PR proteins. A number of signaling molecules, including salicylic acid (SA), ethylene, and jasmonic acid (JA), have been shown to amplify and regulate defense responses in plants during initial activation events, such as oxidative bursts or the expression of PR genes (Johnson et al, 2003;Schenk et al, 2003;Lee and Hwang, 2005).…”
mentioning
confidence: 99%
“…The induced resistance response of plants to diseases correlates intimately with the accumulation of PR proteins. A number of signaling molecules, including salicylic acid (SA), ethylene, and jasmonic acid (JA), have been shown to amplify and regulate defense responses in plants during initial activation events, such as oxidative bursts or the expression of PR genes (Johnson et al, 2003;Schenk et al, 2003;Lee and Hwang, 2005).…”
mentioning
confidence: 99%
“…8). These enhanced defense responses may be activated by various signal transduction pathways, which can be modulated by plant hormones such as SA and JA/ethylene (Lee and Hwang, 2005;Pieterse et al, 2009;. In Arabidopsis, AtPR1 induction depends upon the SAdependent pathway (Glazebrook et al, 1996;Rogers and Ausubel, 1997), whereas AtPDF1.2 is a JA/ethyleneresponsive marker (Penninckx et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…This result suggested that AOS acts as a signal factor for the expression of 尾-1,3-glucanase in cucumber leaves. Lee and Hwang (2005) reported that the co-infiltration of DPI with a virulent pathogen markedly inhibited POD activity as well as H 2 O 2 accumulation. They concluded that the reduction of the H 2 O 2 levels, as a result of DPI application, suppressed the transcription of defense-related genes.…”
Section: Discussionmentioning
confidence: 99%
“…It has been well documented that the development of SAR systems in plants was associated with an oxidative burst, such as the generation of superoxide and subsequent accumulation of H 2 O 2 (Alvarez et al, 1998). It is not yet known whether H 2 O 2 is the primary signal mediator or whether its interactions with other intermediates such as SA and jasmonic acid induce the SAR genes (Lee and Hwang, 2005 Although foliar application of exogenous H 2 O 2 does not play to induce 尾-1,3-glucanase, it was affects on the activation of AOS-mediated enzymes and restriction of powdery mildew infection. The reduction of effectiveness of restriction of powdery mildew by inhibitor of oxidative burst may reflect the critical role of AOS in contributing to the antifungal activity by activation of AOS-mediated enzymes.…”
Section: Discussionmentioning
confidence: 99%